Pyrophosphate and ferric sodium phosphate composite material as well as preparation method and application thereof

By mixing and adding grain growth promoters through the liquid phase method, a nano-sized sodium iron phosphate composite material is formed, which solves the problems of low capacity and poor rate performance of existing materials, and achieves battery materials with high capacity and good rate performance.

CN119797305APending Publication Date: 2025-04-11BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410095449.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-23
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing sodium ferric phosphate materials have low capacity and poor rate performance, mainly due to the low phase purity of the material and the tight morphology of microns, which lead to difficulty in conducting ions and electrons.

Method used

The raw materials are mixed by liquid phase method and grain growth promoters are added to form a material composed of small nano-sized particles through drying and calcining processes, improving the phase purity and electrochemical properties of the material.

Benefits of technology

The high capacity and good rate performance of sodium ferric phosphate pyrophosphate composite material are achieved. The particle size of the material reduces the migration path of ions and electrons, and improves the charging and discharging efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797305A_ABST
    Figure CN119797305A_ABST
Patent Text Reader

Abstract

The invention provides a sodium ferric pyrophosphate composite material as well as a preparation method and application thereof. The preparation method of the pyrophosphate and sodium ferric phosphate composite material comprises the following steps: mixing an iron source, a phosphorus source, a sodium source and a carbon source, and adding water for dissolving to obtain a first mixed solution; adding a grain growth accelerant into the first mixed solution to obtain a second mixed solution; and drying and calcining the second mixed solution to obtain the pyrophosphate ferric phosphate sodium composite material. The preparation method of the pyrophosphate and ferric phosphate sodium composite material provided by the invention is novel, the preparation process is simple, the required raw materials are low in cost, easy to obtain and environment-friendly, and the prepared pyrophosphate and ferric phosphate sodium composite material is high in capacity and good in rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium iron pyrophosphate composite material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries are widely considered to be the next generation of batteries with great application prospects due to their similar principles to lithium-ion batteries and their cost advantages. Sodium resources are relatively abundant and more suitable for large-scale energy storage. Sodium iron pyrophosphate has become the preferred positive electrode material in the energy storage field of the sodium power industry due to its advantages such as abundant phosphorus and iron resources, three-dimensional ion diffusion channels, and long cycle performance.

[0003] At present, the capacity of sodium iron pyrophosphate (Na2FeP2O7) materials on the market is often not high (90-100mAh / g), which is far from the theoretical capacity of 129mAh / g of sodium iron pyrophosphate materials. This is mainly because it is difficult to mix the materials evenly by the traditional solid phase mixing method, and whether the raw materials are uniform directly affects the phase purity of the finished materials. This leads to the low phase purity of the finished materials obtained after calcination, which in turn leads to low capacity. If the liquid phase method and the traditional alkali solution co-precipitation method are used, although the elements can be mixed evenly, thereby improving the phase purity and capacity of sodium iron pyrophosphate, the conventional liquid phase method usually causes the morphology of the material to present a compact micron block after drying, making ion conduction and electronic conduction difficult, and ultimately causing the material rate performance to decline. Summary of the invention

[0004] In view of this, the present application provides a sodium iron pyrophosphate composite material and a preparation method and application thereof. The preparation method has a simple process and can produce a sodium iron pyrophosphate composite material with high capacity and good rate performance.

[0005] In a first aspect, the present application provides a method for preparing a sodium iron pyrophosphate composite material, comprising:

[0006] S1, mixing an iron source, a phosphorus source, a sodium source, and a carbon source, and adding the mixture into water to dissolve the mixture to obtain a first mixed solution;

[0007] S2, adding a grain growth promoter to the first mixed solution to obtain a second mixed solution;

[0008] S3, drying and calcining the second mixed solution to obtain a sodium iron pyrophosphate composite material.

[0009] In one embodiment, in step S1, the iron source includes one or more of ferric nitrate, ferric sulfate, ferric acetate, ferric chloride, ferric citrate, ferric tartrate, and ferric tribromide.

[0010] In one embodiment, in step S1, the sodium source includes one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, sodium pyrophosphate, sodium hexametaphosphate, sodium carbonate, sodium acetate, sodium sulfide, sodium chloride, and sodium sulfate.

[0011] In one embodiment, in step S1, the carbon source includes one or more of glucose, sucrose, polyvinyl pyrrolidone, cellulose, starch, polyethylene glycol, polystyrene, polyvinyl alcohol, polyethylene, polypropylene, citric acid, and stearic acid.

[0012] In one embodiment, in step S1, Na:Fe:P in the first mixed solution is (3.8-4.2):(2.8-3.2):4.

[0013] In one embodiment, in step S1, the carbon source accounts for 2%-20% of the total mass of the iron source, phosphorus source and sodium source.

[0014] In one embodiment, in step S2, the grain growth promoter includes an organic solvent.

[0015] In one embodiment, in step S2, the grain growth promoter includes one or more of N-methylpyrrolidone, dimethylformamide, methanol, ethanol, ethylene glycol, propanol, isopropanol, propylene glycol, n-butanol, acetonitrile, and acetone.

[0016] In one embodiment, in step S2, the volume ratio of the grain growth promoter to the first mixed liquid is (1-10):1.

[0017] In one embodiment, in step S3, drying is performed in a forced air oven at a drying temperature of 80°C-100°C.

[0018] In one embodiment, in step S3, calcination is performed under the protection of a protective gas, and the protective gas includes at least one of helium, neon, argon and nitrogen.

[0019] In one embodiment, in step S3, the calcination temperature is 450°C-600°C, the calcination time is 5h-30h, and the heating rate is 10°C / min.

[0020] The preparation method of the sodium iron pyrophosphate composite material provided by the first aspect of the present invention is novel, and the grains are evenly dispersed and the crystal particles are small by adding a grain growth promoter, the preparation process is simple, the raw materials are cheap and easy to obtain, the environmental pollution is low, and it has high industrial application potential. The sodium iron pyrophosphate composite material prepared by the preparation method has high discharge capacity and good rate performance when used in batteries.

[0021] In a second aspect, the present application provides a sodium iron pyrophosphate composite material, including the sodium iron pyrophosphate composite material prepared by the preparation method described in the first aspect.

[0022] In one embodiment, the particle diameter of the sodium iron pyrophosphate composite material is 20nm-1000nm, and the carbon layer coated on the surface has a carbon content of 1.3%-3.5%.

[0023] In a third aspect, the present application provides a positive electrode material, which includes the sodium iron pyrophosphate composite material prepared by the preparation method described in the first aspect or the sodium iron pyrophosphate composite material described in the second aspect.

[0024] In a fourth aspect, the present application provides a battery, comprising the sodium iron pyrophosphate composite material of the second aspect of the present application or the positive electrode material of the third aspect of the present application. The sodium iron pyrophosphate composite material obtained in the present application has high discharge capacity and good rate performance when used in a battery.

[0025] In a fifth aspect, the present application provides an electrical device, comprising the positive electrode material provided in the third aspect of the present application or the battery provided in the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the embodiments or the prior art description. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0027] Figure 1 This is the X-ray diffraction analysis spectrum of the sodium iron pyrophosphate composite material provided in Example 1 of the present application.

[0028] Figure 2 This is a scanning electron microscope image of the sodium iron pyrophosphate composite material provided in Example 1 of the present application, with a scale of 1 μm.

[0029] Figure 3 This is the magnification cycle test image provided in Example 1 of the present application. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0031] In the current technologies related to positive electrode materials, the capacity of sodium iron pyrophosphate materials is often not high (90-100mAh / g), which is far from the theoretical capacity of 129mAh / g of sodium iron pyrophosphate materials. This is mainly because it is difficult to mix the materials evenly by the traditional solid phase mixing method, and whether the raw materials are uniform directly affects the phase purity of the finished materials, which leads to the low phase purity of the finished materials currently obtained, and then leads to low capacity. If the liquid phase method and the traditional alkali solution co-precipitation method are used, although the elements can be mixed evenly, thereby improving the phase purity and capacity of sodium iron pyrophosphate, the conventional liquid phase method usually causes the morphology of the material to present a compact micron block after drying, making ion conduction and electronic conduction difficult, and ultimately causing the material rate performance to decline.

[0032] In order to solve the above technical problems, the present application provides a method for preparing a sodium iron pyrophosphate composite material, comprising:

[0033] S1, mixing an iron source, a phosphorus source, a sodium source, and a carbon source, and adding the mixture into water to dissolve the mixture to obtain a first mixed solution;

[0034] S2, adding a grain growth promoter to the first mixed solution to obtain a second mixed solution;

[0035] S3, drying and calcining the second mixed solution to obtain a sodium iron pyrophosphate composite material.

[0036] Compared with the existing technical solutions, this solution uses soluble raw materials for liquid phase mixing, and the elements are evenly distributed, which is beneficial to improve the phase purity of the calcined material. At the same time, a grain growth promoter is added. The grain promoter is usually composed of an organic solvent with low material solubility. After the grain promoter is added, due to the sudden change in the solubility of the solution, a large number of original grains will be produced. In the subsequent further drying and crystallization process, due to the large number of original grains and the competition between the original grains during grain growth, the growth of each grain is limited, so that the material finally presents a morphology composed of nano-scale small particles. Smaller particle size can effectively shorten the migration path of ions and electrons during charging and discharging, which is beneficial to the rapid conduction of ions and electrons. Therefore, the material has better capacity performance and rate performance.

[0037] In one embodiment, the iron source includes one or more of ferric nitrate, ferric sulfate, ferric acetate, ferric chloride, ferric citrate, ferric tartrate, and ferric tribromide. The above iron sources can all provide iron elements and have a certain solubility in water. Preferably, the iron source can be selected from ferric nitrate, which is an inorganic iron salt whose iron ions are trivalent and have high water solubility. Using ferric nitrate as an iron source, a sodium ferric pyrophosphate product with higher purity can be obtained.

[0038] In one embodiment, the sodium source includes one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, sodium pyrophosphate, sodium hexametaphosphate, sodium carbonate, sodium acetate, sodium sulfide, sodium chloride, and sodium sulfate. The above sodium sources can all provide sodium elements and have good solubility in water, which is beneficial to improving the purity of the product.

[0039] In one embodiment, the carbon source includes one or more of glucose, sucrose, polyvinyl pyrrolidone, cellulose, starch, polyethylene glycol, polystyrene, polyvinyl alcohol, polyethylene, polypropylene, citric acid, and stearic acid. The above carbon sources are all soluble carbon sources, which can provide carbon atoms required for synthesis, participate in chemical reactions, and generate required compounds. Secondly, different carbon sources have different physical and chemical properties, and selecting a suitable carbon source can affect the quality and purity of the final product. For example, simple sugar substances such as glucose and sucrose can quickly provide the carbon source required for synthesis, while polymer compounds such as cellulose and polyvinyl pyrrolidone can provide more carbon atoms. In addition, selecting a renewable carbon source can also reduce preparation costs and is beneficial to environmental protection. For example, using natural polymer compounds such as starch and cellulose as carbon sources can not only reduce costs, but also these substances can be derived from renewable plant resources. Therefore, selecting a suitable carbon source can optimize the preparation process, improve the quality and purity of the product, reduce costs and be beneficial to environmental protection.

[0040] In one embodiment, the ratio of sodium, iron and phosphorus in the first mixed solution satisfies Na:Fe:P=(3.8-4.2):(2.8-3.2):4. The standard element ratio of sodium ferric pyrophosphate is 4:3:4, but depending on the raw materials, the element ratio can be optimized and slightly adjusted, and the electrochemical properties of the material can be further optimized. Optionally, the ratio of Na:Fe:P can be 3.8:2.8:4, 3.9:2.9:4, 4.0:2.9:4, 4.1:2.9:4, 4:3:4, 4.2:3.1:4 and 4.0:3.2:4.

[0041] In one embodiment, the carbon source accounts for 2%-20% of the total mass of the iron source, phosphorus source, and sodium source. The carbon source needs to be determined according to the type of carbon source and the carbon retention rate so that the residual amount after calcination is within an appropriate range. The carbon source can avoid excessive polarization of the material and incomplete reaction within this range, and will not cause a decrease in the material mass specific capacity. Optionally, the carbon source can account for 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20% of the total mass of the iron source, phosphorus source, and sodium source.

[0042] In one embodiment, the mass ratio of the carbon source, iron source, phosphorus source, sodium source and water is (1-10):1, so as to ensure that the raw materials can be completely dissolved and mixed evenly, which is beneficial to the physical purity of the subsequent materials. Optionally, the mass ratio of the carbon source, iron source, phosphorus source, sodium source and water can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10.

[0043] In one embodiment, the grain growth promoter includes one or more of N-methylpyrrolidone, dimethylformamide, methanol, ethanol, ethylene glycol, propanol, isopropanol, propylene glycol, n-butanol, acetonitrile, and acetone. The solubility of the precursor material of sodium ferric pyrophosphate in these solvents is low. Therefore, after adding these solvents, the precursor material will be more easily precipitated and crystallized, which is beneficial to the formation of original grains. The above-mentioned precursor materials are the iron source, phosphorus source, sodium source, and carbon source in step S1.

[0044] In one embodiment, the volume ratio of the grain growth promoter to the first mixed solution is (1-10): 1. The ratio of the grain growth promoter to the first mixed solution has a great influence on the formation of the original grains of the precursor in step S2 and the grain size of the subsequent finished material. The grain size of the finished material can be regulated by adding the amount of the grain growth promoter. When the amount of the grain growth promoter added is within this range, it is conducive to the formation of the original grains and reduces the grain size of the finished material. Optionally, the volume ratio of the grain growth promoter to the first mixed solution can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1.

[0045] In one embodiment, drying is carried out in a blast oven at a drying temperature of 80°C-100°C and a drying time of 5 hours-10 hours. Drying under these conditions can effectively remove excess grain growth promoters, thereby obtaining dried sodium iron pyrophosphate powder, and will not cause denaturation of the sodium iron pyrophosphate powder. Optionally, the drying temperature can be 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C, 96°C, 98°C, 100°C, and the drying time can be 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h. In another embodiment of the present invention, drying can also be carried out by spray drying.

[0046] In one embodiment, the calcination is carried out under the protection of a protective gas, and the protective gas includes at least one of helium, neon, argon and nitrogen. The sodium iron pyrophosphate material will rapidly decompose in an oxidizing environment to produce iron-containing oxides. Therefore, a protective gas is required for protection during the calcination process to prevent the entry of air.

[0047] In one embodiment, the calcination temperature is 450°C-600°C, the calcination time is 5h-30h, and the heating rate is 5-20°C / min. Calcination is a necessary process for preparing the finished product of the sodium iron pyrophosphate material. The precursor with uniformly mixed elements in step S3 (specifically the product after drying in step S3) will melt and react under the action of high temperature, and finally form the finished powder of sodium iron pyrophosphate. Under this calcination condition, it is beneficial to the crystallinity, phase purity and electrochemical properties of the material. Optionally, the calcination temperature can be 450℃, 470℃, 490℃, 510℃, 530℃, 550℃, 570℃, 590℃, 600℃; the calcination time can be 5h, 8h, 11h, 14h, 17h, 20h, 23h, 26h, 29h, 32h, 35h; and the heating rate can be 5℃ / min, 8℃ / min, 10℃ / min, 12℃ / min, 14℃ / min, 15℃ / min, 16℃ / min, 18℃ / min, 20℃ / min.

[0048] In a second aspect, the present application provides a sodium iron pyrophosphate composite material, including the sodium iron pyrophosphate composite material prepared by the preparation method described in the first aspect. The sodium iron pyrophosphate composite material is used in a battery with high discharge capacity and good rate performance.

[0049] In one embodiment, the particle diameter of the sodium iron pyrophosphate composite material is 20nm-1000nm, and the carbon content is 1.3%-3.5%. The carbon content plays a key role in regulating the electronic conduction rate of the material. When the carbon content further meets the range of this embodiment, the electronic conduction of the material is better, the rate performance is better and the capacity of the material will not be significantly reduced. Optionally, the particle diameter of the sodium iron pyrophosphate composite material can be 20nm, 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm; Optionally, the carbon content of the sodium iron pyrophosphate composite material is 1.3%, 1.5%, 1.7%, 2.0%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 3.0%, 3.2%, 3.5%.

[0050] In a third aspect, the present application provides a sodium ion battery positive electrode material, the sodium ion battery positive electrode material comprising the sodium iron pyrophosphate composite material prepared by the preparation method described in the first aspect or the sodium iron pyrophosphate composite material described in the second aspect. The preparation method of the sodium iron pyrophosphate composite material provided in the present application is novel, the preparation process is simple, the raw materials are cheap and readily available, the environmental pollution is low, and it has a high potential for industrial application. The sodium iron pyrophosphate composite material prepared by the preparation method has a high discharge capacity and good rate performance when used in batteries.

[0051] In a fourth aspect, the present application provides a battery, comprising the sodium iron pyrophosphate composite material of the second aspect of the present application or the positive electrode material of the third aspect of the present application. The sodium iron pyrophosphate composite material obtained in the present application has high discharge capacity and good rate performance when used in a battery.

[0052] In a fifth aspect, the present application provides an electrical device, comprising the positive electrode material provided in the third aspect of the present application or the battery provided in the fourth aspect of the present application.

[0053] The effect of the technical solution of the present application is further illustrated below through specific examples.

[0054] Example 1

[0055] (1) Preparation of precursor aqueous solution: Select ferric nitrate (Fe(NO3)3·9H2O) as the iron source, sodium dihydrogen phosphate (NaH2PO4·2H2O) as the phosphorus source and sodium source respectively, the specific dosage is 2 mol sodium dihydrogen phosphate, 1.456 mol ferric nitrate, and glucose is selected as the organic carbon source, the dosage is 90g, the above raw materials are added to 100ml of water to form a first mixed solution, and heated to 80°C, stirred for more than 10min, until the solution is clear and uniform. At this time, Na:Fe:P in the first mixed solution is 4:2.912:4, the carbon source accounts for 10% of the total mass of the iron source, phosphorus source, and sodium source, and the mass ratio of carbon source, iron source, phosphorus source, sodium source and water is about 10:1.

[0056] (2) Select ethanol as a grain growth promoter, and slowly add 500 ml of ethanol into the precursor aqueous solution through a peristaltic pump. After all the ethanol is added, continue stirring for 30 minutes. The volume ratio of the grain growth promoter to the first mixed solution is 5:1.

[0057] (3) The suspension solution obtained in step (2) was stirred and dried in an oven at 80° C. to obtain a precursor powder.

[0058] (4) The precursor powder in step (3) is placed in a tube furnace, heated to 500°C at a heating rate of 10°C / min, and kept warm for 10 hours to finally obtain a finished material powder. Figure 1 The X-ray diffraction spectrum of the target product synthesized in this example shows that the target product is a pure phase sodium iron pyrophosphate material, and no obvious diffraction peaks of impurities are found. Figure 2 This is a SEM image of the target product synthesized in this example. It can be seen from the figure that the target product is composed of small particles of 20-100nm. The CS test (carbon content test) shows that the carbon content of the material after calcination is 2.1%.

[0059] (5) Assembling the battery: Using the sodium iron pyrophosphate powder prepared above as the positive electrode active material, the positive electrode active material: conductive agent (specifically conductive carbon black): binder (specifically PVDF) = 90:5:5 are mixed, and the electrode is prepared by coating-rolling operation; the electrode is subsequently used as the positive electrode, the metal sodium is used as the negative electrode, and the glass fiber is used as the separator to assemble a half-cell. Test performance is as follows Figure 3 shown.

[0060] Example 2

[0061] (1) Preparation of precursor aqueous solution: Select ferrous sulfate (Fe2(SO4)3·9H2O), phosphoric acid (H3PO4) and disodium hydrogen phosphate (Na2HPO4·2H2O) as raw materials, the specific amount is 1.03 mol disodium hydrogen phosphate, 0.97 mol phosphoric acid, 1.5 mol ferrous sulfate, and sucrose is selected as an organic carbon source, the amount is 54.93 g, the above raw materials are added to 200 ml of water, and heated to 80 ° C, stirred for more than 10 minutes, until the solution is clear and uniform. At this time, Na:Fe:P in the first mixed solution is 4.12:3:4, the carbon source accounts for 5% of the total mass of the iron source, phosphorus source, and sodium source, and the mass ratio of carbon source, iron source, phosphorus source, sodium source and water is about 5.76:1.

[0062] (2) Select dimethylformamide (DMF) as a grain growth promoter, and slowly add 400 ml of dimethylformamide (DMF) into the precursor aqueous solution through a peristaltic pump. After all the DMF is added, continue stirring for 30 minutes. The volume ratio of the grain growth promoter to the first mixed solution is 2:1.

[0063] Steps (3), (4) and (5) remain the same as in Example 1.

[0064] Example 3

[0065] (1) Preparation of precursor aqueous solution: Select ferric acetate (Fe(CH3COO)3) and sodium dihydrogen phosphate (NaH2PO4·2H2O) as raw materials, the specific amount is 2 mol sodium dihydrogen phosphate, 1.52 mol ferric acetate, and glucose is selected as an organic carbon source, the amount is 65.1 g, the above raw materials are added to 71 ml of water, and heated to 80 ° C, stirred for more than 10 minutes, until the solution is clear and uniform. At this time, Na:Fe:P in the first mixed solution is 4:3.04:4, the carbon source accounts for 5% of the total mass of the iron source, phosphorus source, and sodium source, and the mass ratio of carbon source, iron source, phosphorus source, sodium source and water is about 10:1.

[0066] (2) Select ethanol as a grain growth promoter, and slowly add 500 ml of ethanol into the precursor aqueous solution through a peristaltic pump. After all the ethanol is added, continue stirring for 30 minutes. The volume ratio of the grain growth promoter to the first mixed solution is 5:1.

[0067] Steps (3), (4) and (5) remain the same as in Example 1.

[0068] Example 4

[0069] (1) Preparation of precursor aqueous solution: Select ferric nitrate (Fe(NO3)3·9H2O), phosphoric acid (H3PO4) and sodium pyrophosphate (Na4P2O7) as raw materials, the specific amount is 0.5 mol sodium pyrophosphate, 1 mol phosphoric acid, 1.456 mol ferric nitrate, and select glucose as an organic carbon source, the amount is 162.4 g, add the above raw materials to 100 ml of water, and heat to 80 ° C, stir for more than 10 minutes, until the solution is clear and uniform. At this time, Na:Fe:P in the first mixed solution is 4:2.912:4, the carbon source accounts for 20% of the total mass of the iron source, phosphorus source, and sodium source, and the mass ratio of carbon source, iron source, phosphorus source, sodium source and water is about 10:1.

[0070] (2) Select ethanol as a grain growth promoter, and slowly add 500 ml of ethanol into the precursor aqueous solution through a peristaltic pump. After all the ethanol is added, continue stirring for 30 minutes. The volume ratio of the grain growth promoter to the first mixed solution is 5:1.

[0071] Steps (3), (4) and (5) remain the same as in Example 1.

[0072] Example 5

[0073] The difference from Example 1 is that the amount of the grain growth promoter added in step (2) is 1000 ml, and the volume ratio of the grain growth promoter to the first mixed liquid is 10:1.

[0074] Example 6

[0075] The difference from Example 1 is that the amount of the grain growth promoter added in step (2) is 100 ml, and the volume ratio of the grain growth promoter to the first mixed solution is 1:1.

[0076] Example 7

[0077] The difference from Example 1 is that the amount of the grain growth promoter added in step (2) is 50 ml, and the volume ratio of the grain growth promoter to the first mixed solution is 0.5:1.

[0078] Comparative Example 1

[0079] (1) Preparation of precursor aqueous solution: Select ferric nitrate (Fe(NO3)3·9H2O) and sodium dihydrogen phosphate (NaH2PO4·2H2O) as raw materials, with a specific dosage of 2 mol sodium dihydrogen phosphate and 1.456 mol ferric nitrate. At the same time, select glucose as the organic carbon source, with an dosage of 90 g. Add the above raw materials into 100 ml of water, heat to 80°C, and stir for 10 min until the solution is clear and uniform.

[0080] (2) The solution obtained in step (1) was stirred and dried in an oven at 80° C., and then ground to obtain a precursor powder.

[0081] (3) The precursor powder in step (3) is placed in a tubular furnace, heated to 500° C. at a heating rate of 10° C. / min, and kept at this temperature for 10 h to finally obtain a finished material powder.

[0082] (4) Assembling a battery: Using the sodium iron pyrophosphate powder prepared above as the positive electrode active material, the mixture is mixed in a ratio of positive electrode active material: conductive agent (specifically conductive carbon black): binder (specifically PVDF) = 90:5:5, and then prepared into an electrode through operations such as coating and rolling; subsequently, the electrode is used as the positive electrode, metallic sodium is used as the negative electrode, and glass fiber is used as the separator to assemble into a half-cell.

[0083] Performance Testing

[0084] SEM (Scanning Electron Microscope) test: The particles of the sodium iron pyrophosphate composite material were characterized under a scanning electron microscope (JEOL SEM-200201 scanning electron microscope). The particles of the obtained sodium iron pyrophosphate composite material were observed under a scanning electron microscope to obtain the particle diameter range of the sodium iron pyrophosphate composite material. The test results are shown in Table 1.

[0085] C content test: The C content of the sodium iron pyrophosphate composite material was analyzed and tested using an infrared absorption carbon-sulfur analyzer (HORIBAEMIA-Pro high-frequency infrared carbon-sulfur analyzer) in accordance with the test standard of GB / T20123-2006. The test results are shown in Table 1.

[0086] XRD test (X-ray diffraction): The finished powder is tested using a powder X-ray diffraction tester (BRUKERD8ADVANCE XRD diffraction analyzer) to obtain the phase information of the sodium iron pyrophosphate composite material.

[0087] Rate performance test: The batteries prepared in each embodiment and comparative example were subjected to charge and discharge cycle test at 298±1K on the LAND CT 2001C secondary battery performance test device at current densities of 0.1C, 0.5C, 1C, and 2C (1C = 129mA / g). The steps are as follows: stand for 10 minutes; charge at a constant current until 4V is cut off, then discharge at a constant current until 2V is cut off, cycle 5 times at each current density, and record the stable capacity (mAh / g) after cycling at each current density. The test results are shown in Table 2.

[0088] Table 1 Scanning electron microscope test results

[0089] Particle diameter (nm) Carbon content (%) Example 1 About 20nm-100nm 2.1% Example 2 About 100nm-400nm 1.3% Example 3 About 20nm-100nm 2.6% Example 4 About 20nm-100nm 3.5% Example 5 About 20nm-100nm 2.0% Example 6 About 300nm-1000nm 2.1% Example 7 About 700nm-3000nm 2.1% Comparative Example 1 >5μm, and severely agglomerated 2.1%

[0090] Table 2 Rate test results

[0091]

[0092] Note: Current density 1C = 129mA / g

[0093] Based on the above test results, we can find that the particle size and carbon content of the material have a great influence on the rate performance of the material, especially the particle size. When the grain growth promoter is not added and directly dried, the particle size of the material cannot be suppressed and agglomeration is serious, resulting in the growth of ion diffusion and electron conduction paths, and finally causing serious degradation of the battery rate performance. By comparing Examples 1, 5, 6, and 7, it can be seen that the ratio of the grain growth promoter to the first mixed solution also has an effect on the grain size and rate cycle performance. The higher the amount of the grain growth promoter, the smaller the grain of the finished material; but when the grain growth promoter and the first mixed solution further meet the volume ratio of (1-10): 1, the rate cycle performance is more excellent.

[0094] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A method for preparing a sodium iron pyrophosphate composite material, characterized in that: The following steps are involved: S1, mixing an iron source, a phosphorus source, a sodium source, and a carbon source, and adding the mixture into water to dissolve the mixture to obtain a first mixed solution; S2, adding a grain growth promoter to the first mixed solution to obtain a second mixed solution; S3, drying and calcining the second mixed solution to obtain a sodium iron pyrophosphate composite material.

2. The preparation method according to claim 1, characterized in that In step S1, the iron source includes one or more of ferric nitrate, ferric sulfate, ferric acetate, ferric chloride, ferric citrate, ferric tartrate, and ferric tribromide.

3. The preparation method according to claim 1, characterized in that: In step S1, the sodium source includes one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, sodium pyrophosphate, sodium hexametaphosphate, sodium carbonate, sodium acetate, sodium sulfide, sodium chloride, and sodium sulfate.

4. The preparation method according to claim 1, characterized in that: In step S1, the carbon source includes one or more of glucose, sucrose, polyvinyl pyrrolidone, cellulose, starch, polyethylene glycol, polystyrene, polyvinyl alcohol, polyethylene, polypropylene, citric acid, and stearic acid.

5. The preparation method according to claim 1, characterized in that: In step S1, the ratio of sodium, iron and phosphorus in the first mixed solution satisfies Na:Fe:P=(3.8-4.2):(2.8-3.2):

4.

6. The preparation method according to claim 1, characterized in that: In step S1, the carbon source accounts for 2%-20% of the total mass of the iron source, phosphorus source and sodium source.

7. The preparation method according to claim 1, characterized in that: In step S2, the grain growth promoter includes an organic solvent.

8. The preparation method according to claim 7, characterized in that: The organic solvent includes one or more of N-methylpyrrolidone, dimethylformamide, methanol, ethanol, ethylene glycol, propanol, isopropanol, propylene glycol, n-butanol, acetonitrile and acetone.

9. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the grain growth promoter to the first mixed liquid is (1-10):

1.

10. The preparation method according to claim 1, characterized in that: In step S3, the drying is carried out in a blast oven at a drying temperature of 80°C-100°C.

11. The preparation method according to claim 1, characterized in that: In step S3, the calcination is performed under the protection of a protective gas, and the protective gas includes at least one of helium, neon, argon and nitrogen.

12. The preparation method according to claim 1, characterized in that: In step S3, the calcination temperature is 450°C-600°C, the heating rate is 5-20°C / min, and the calcination time is 5h-30h.

13. A sodium iron pyrophosphate composite material, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 12.

14. The sodium iron pyrophosphate composite material according to claim 13, characterized in that The particle diameter of the sodium iron pyrophosphate composite material is 20nm-1000nm, and the carbon content is 1.3%-3.5%.

15. A positive electrode material, characterized in that: The positive electrode material includes the sodium iron pyrophosphate composite material obtained by the preparation method according to any one of claims 1 to 12 or the sodium iron pyrophosphate composite material according to any one of claims 13 or 14.

16. A battery, characterized in that: The battery comprises the sodium iron pyrophosphate composite material of claim 13 or 14 or the positive electrode material of claim 15.

17. An electrical device, characterized in that: The electrical device comprises the positive electrode material according to claim 15 or the battery according to claim 16.